PENDIDIKAN TRANSFORMATIF DI ERA DIGITAL: OPTIMALISASI PERUBAHAN MINDSET SISWA MENGGUNAKAN TRELLO DALAM MATERI ISMUBA - MOHAMMAD JAILANI; Dwi Sulisworo (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2025)
Abstract The urgency of transforming education in the digital era is increasingly relevant due to technological advancements that drive changes in learning methods. The use of digital platforms, such as TRELLO, provides opportunities to optimize shifts in student mindsets in learning, particularly in the subject of Ismuba (Islamic Studies, Muhammadiyah Studies, and Arabic Language). This transformation in learning aims to enhance active student engagement, critical thinking skills, and collaboration through integrating technology that aligns with the characteristics of the digital age. This research aims to explore and evaluate the use of TRELLO as a learning aid to facilitate changes in student mindsets in Ismuba education. Through a narrative review approach, this study analyses various literature related to implementing technology in education, mindset changes, and the application of TRELLO in the context of Islamic education. Data was collected from various relevant academic and practical sources. The findings suggest that TRELLO, as a learning medium, can have a positive impact on changing students’ mindsets to be more proactive, innovative, and organized. TRELLO, with its collaborative features, also helps create a more interactive and organized learning environment, making it easier for students to follow the learning flow more effectively. The conclusion of this research states that the use of TRELLO in Ismuba education can support a more effective educational transformation process in the digital era. The integration of this digital platform not only increases students’ motivation to learn but also teaches them essential management and collaboration skills needed for the future. The contribution of this research is to provide practical guidance for educators in leveraging technology, particularly TRELLO, to enhance the quality of Ismuba education and foster a more adaptive mindset among students in response to change.   Abstrak Urgensi transformasi pendidikan di era digital semakin relevan dengan kemajuan teknologi yang mendorong perubahan dalam metode pembelajaran. Penggunaan platform digital, seperti TRELLO, memberikan peluang untuk mengoptimalkan perubahan mindset siswa dalam pembelajaran, khususnya dalam mata pelajaran Ismuba (Al-Islam, Kemuhammadiyahan, dan Bahasa Arab). Transformasi pembelajaran ini bertujuan untuk meningkatkan keterlibatan aktif siswa, kemampuan berpikir kritis, dan kolaborasi melalui integrasi teknologi yang sesuai dengan karakteristik era digital. Penelitian ini bertujuan untuk mengeksplorasi dan mengevaluasi penggunaan TRELLO sebagai alat bantu pembelajaran untuk memfasilitasi perubahan mindset siswa dalam pembelajaran Ismuba. Melalui pendekatan narrative review, penelitian ini menganalisis berbagai literatur terkait implementasi teknologi dalam pendidikan, perubahan mindset, dan penerapan TRELLO dalam konteks pendidikan Islam. Data dikumpulkan dari berbagai sumber akademis dan praktis yang relevan. Hasil penelitian menunjukkan bahwa TRELLO sebagai media pembelajaran dapat memberikan dampak positif dalam mengubah mindset siswa menjadi lebih proaktif, inovatif, dan terstruktur. TRELLO juga membantu menciptakan lingkungan pembelajaran yang kolaboratif dan terorganisir, serta memudahkan siswa untuk mengikuti alur pembelajaran dengan lebih baik. Kesimpulan dari penelitian ini menyatakan bahwa penggunaan TRELLO dalam pembelajaran Ismuba dapat mendukung proses transformasi pendidikan yang lebih efektif di era digital. Integrasi platform digital ini tidak hanya meningkatkan motivasi belajar siswa, tetapi juga mengajarkan mereka keterampilan manajemen dan kolaborasi yang diperlukan di masa depan. Kontribusi penelitian ini adalah memberikan panduan praktis bagi para pendidik dalam memanfaatkan teknologi, khususnya TRELLO, untuk meningkatkan kualitas pembelajaran Ismuba dan membentuk mindset siswa yang lebih adaptif terhadap perubahan.